Editorial: clinical outcomes in lean NAFLD—the devil is in the details. Issue 9 (13th April 2023) - Tan, Eunice X. X.; Muthiah, Mark Dhinesh; Ng, Cheng Han; Huang, Daniel Q.
LINKED CONTENT: This article is linked to Wijarnpreecha et al papers. To view these articles, visit https://doi.org/10.1111/apt.17424 and https://doi.org/10.1111/apt.17453